CAMPAIGN UPDATE NO ON PROPOSITION P (Tufts Archival Research Center, 2007)
Confidential; Nelson-Padberg Consulting campaign update on "No on Proposition P," opposing a proposed local ordinance against smoking in the workplace, for San Franciscans Against Government Intrusion. Discusses budget, campaign organization, research and advertising and direct voter contact. Also covers endorsements, ballot arguments, the news bureau, the speakers bureau, and fundraising. Summarizes what has been done to date and what still needs to be done.